2014
DOI: 10.1152/ajpgi.00401.2013
|View full text |Cite
|
Sign up to set email alerts
|

Converging effects of a Bifidobacterium and Lactobacillus probiotic strain on mouse intestinal physiology

Abstract: Evidence has grown to support the efficacy of probiotics in the management of gastrointestinal disorders, many of which are associated with dysregulated fluid and electrolyte transport. A growing body of evidence now suggests that the host microbiota and probiotics can influence intestinal ion transport and that these effects often occur in a strain-dependent manner. In this study, we sought to investigate the effects of two therapeutically relevant organisms, Bifidobacterium infantis 35624 and Lactobacillus s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(21 citation statements)
references
References 39 publications
1
20
0
Order By: Relevance
“…All of these probiotics are regarded as "good" bacteria, presumably inhibiting the growth of harmful bacteria or pathogens and/or improving the immune system. [67][68][69] These probiotics were also found to reduce the symptoms of gastrointestinal disease, such as irritable bowel syndrome. 15,16,58,70 Probiotics may play an important role in gut-brain axis communication, thereby benefiting both the brain and the gut.…”
Section: Effects Of Probioticsmentioning
confidence: 99%
“…All of these probiotics are regarded as "good" bacteria, presumably inhibiting the growth of harmful bacteria or pathogens and/or improving the immune system. [67][68][69] These probiotics were also found to reduce the symptoms of gastrointestinal disease, such as irritable bowel syndrome. 15,16,58,70 Probiotics may play an important role in gut-brain axis communication, thereby benefiting both the brain and the gut.…”
Section: Effects Of Probioticsmentioning
confidence: 99%
“…The collected data from previous studies demonstrated that alterations in the gut microflora can lead to GI disorders (19). Dietary components may influence microflora balance and modification (4,20), which can in turn reduce the incidence of several problems in the GI (3). Undeniably, greater attention is needed about the exposure duration of beneficial probiotics for health promotion (4,9).…”
Section: Discussionmentioning
confidence: 99%
“…As described previously [20, 21], the dry-wet ratio of feces was measured to determine gastrointestinal transition rate in WT, β 1/2 -AR KO, and M 2/3 -R KO mice. Mice were separately placed in cages with wire flooring insets and allowed ad libitum access to water and food.…”
Section: Methodsmentioning
confidence: 99%